GLOBAL BURDEN, REGIONAL DIFFERENCES, TRENDS, AND HEALTH CONSEQUENCES OF MEDICATION NON-ADHERENCE IN PATIENTS WITH HYPERTENSION DURING 2010-2020: A SYSTEMATIC REVIEW AND META-ANALYS. (June 2022) - Lee, Eric Kam-Pui; Poon, Paul; Bo, Yacong; Zhu, Meng-Ting; Yu, Chun-Pong; Ngai, Alfonse Ch; Wong, Martin Cs; Wong, Samuel Ys
Abstract : Objective: Non-adherence to anti-hypertensive medications (anti-HT non-adherence) is the leading cause of poor blood pressure (BP) control, and thereby cardiovascular diseases and mortality worldwide. This study aims to investigate the global epidemiology of anti-HT non-adherence. Design and method: This study comprises a systematic review and meta-analysis investigating global prevalence, regional differences, and trends of anti-HT non-adherence in 2010–2020. Multiple medical databases and clinicaltrial.gov were searched for articles with a cut-off of December 2020. Observational studies reporting the proportion of patients with anti-HT non-adherence were included. The proportion of non-adherence, publication year, year of first recruitment (for trend analysis), country, and health outcomes due to anti-HT non-adherence were extracted. Two independent reviewers conducted abstract and full text screening, classified countries according to levels of income and locations and extracted data. Meta-analyses were conducted using a random effect model and trends of prevalence were analysed using meta-regression. Results: A total of 161 studies, including more than 27 million participants were included. The global prevalence of anti-HT non-adherence was 43% (95%CI: 40–45%, I2: 99·98%, p < 0·001). Non-adherence was more prevalent in low-to-middle-income countries than in high-income countries (47% vs. 38%, meta-regression p = 0·002), and in non-Western countries than in Western countries (46% vs. 36%, p = 0·002). No significant trend in prevalence was detected during 2010–2020. Patients with anti-HT non-adherence had suboptimal BP control (OR 2·15, 95%CI: 1·84–2·5, I2: 97·4%, p < 0·001), complications from HT (OR 2·08, 95%CI: 0·99–4.35, I2: 94·2%, p < 0.001), all-cause hospitalisation (OR 1·38, 95%CI: 1·35–1·41, I2: 0, p = 0·64), and all-cause mortality (OR 1·38, 95%CI: 1·35–1·41, I2: 0, p = 0·509). Conclusions: While a high prevalence of anti-HT non-adherence was detected worldwide, a higher prevalence was detected in low-to-middle-income and non-Western countries. Interventions are urgently required, especially in these regions. Current evidence is limited by high heterogeneity.